Xylem Vessel Diameter Affects the Compartmentalization of the Vascular Pathogen Phaeomoniella chlamydospora in Grapevine - Pouzoulet, Jérôme; Scudiero, Elia; Schiavon, Marco; Rolshausen, Philippe E. (Frontiers in Plant Science, 2017)
Fungal wilt diseases are a threat to global food safety. Previous studies in perennials crops showed that xylem vessel diameter affects disease susceptibility. We tested the hypothesis that xylem vessel diameter impacts occlusion processes and pathogen compartmentalization in Vitis vinifera L. We studied the interaction between four grape commercial cultivars with the vascular wilt pathogen Phaeomoniella chlamydospora. We used qPCR and wood necrotic lesion length to measure fungal colonization coupled with histological studies to assess differences in xylem morphology, pathogen compartmentalization, and fungal colonization strategy. We provided evidence that grape cultivar with wide xylem vessel diameter showed increased susceptibility to P. chlamydospora. The host response to pathogen included vessel occlusion with tyloses and gels, deposition of non-structural phenolic compounds and suberin in vessel walls and depletion of starch in parenchyma cells. Pathogen compartmentalization was less efficient in wide xylem vessels than in narrow diameter vessels. Large vessels displayed higher number of tyloses and gel pockets, which provided substrate for P. chlamydospora growth and routes to escape occluded vessels. We discuss in which capacity xylem vessel diameter is a key determinant of the compartmentalization process and in turn grape cultivar resistance to disease caused by P. chlamydospora.